2021
DOI: 10.3390/ijerph18073666
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Face Coverings in Mitigating the COVID-19 Pandemic in the United States

Abstract: The COVID-19 pandemic has been one of the biggest public health challenges of the 21st century. Many prevalent measures have been taken to prevent its spread and protect the public. However, the use of face coverings as an effective preventive measure remains contentious. The goal of the current study is to evaluate the effectiveness of face coverings as a protective measure. We examined the effectiveness of face coverings between 1 April and 31 December 2020. This was accomplished by analyzing trends of daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…All studies reported a protective benefit in terms of either reduced incidence, mortality, hospitalization, or a combination of these outcomes. This review summarized the literature up to March 2021, since which time a number of additional studies have reported a protective benefit impact of community mask wearing by the general public in community settings using ecological data [42] , [43] , [44] , [45] , [46] . While the results of these individual studies support the findings of this review, the large amount of research being done to assess community mask wearing warrants future systematic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported a protective benefit in terms of either reduced incidence, mortality, hospitalization, or a combination of these outcomes. This review summarized the literature up to March 2021, since which time a number of additional studies have reported a protective benefit impact of community mask wearing by the general public in community settings using ecological data [42] , [43] , [44] , [45] , [46] . While the results of these individual studies support the findings of this review, the large amount of research being done to assess community mask wearing warrants future systematic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Infections with coronaviruses remain a burden negatively affecting human life. The 2 major routes of transmission are airborne and direct contact ( Ayodeji and Ramkumar, 2021 ) but the dominant route is airborne ( Zhang et al, 2020 ). While the effectiveness of ZnO coatings on surfaces to prevent fomite transmission of SARS-CoV-2 has been reported, the use of ZnO in barrier face coverings to control the airborne spread of the virus has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of the COVID-19 pandemic has significantly impacted the social interactions, economy, culture, and health of billions of people around the globe (Gopalan and Misra 2020 ; Mofijur et al 2021 ). During the outbreak, widespread lockdowns, physical and social distancing (Drewnick et al 2021 ; Marroquin et al 2020 ), travel restrictions (Beck and Hensher 2020 ), and wearing of face coverings (Ayodeji and Ramkumar 2021 ; Zhang et al 2020 ) were the major mitigation measures to protect public health. The wearing of face coverings followed recommendations from the World Health Organization and the United States Centers for Disease Control (CDC) that barrier face coverings protect both the wearer and others from infection through exposure to droplets and aerosols carrying infectious virus (CDC 2020a ; b ; WHO 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%